Estrategias de difusión del legado histórico cultural de la poetisa aurora estrada para el desarrollo del turismo cultural - Cornejo Vera, Jenifer Estefania (2021)
In the recent research work, the Strategies for the dissemination of the Cultural Historical Legacy of the poet Aurora Estrada are observed, in order to promote the development of Cultural Tourism in the Puebloviejo canton of the Province of Los Ríos, to spread knowledge about important literary authors for the canton and the country, thus promoting tourism. The different Strategies of Diffusion of the Cultural Historical Legacy of the poet Aurora Estrada for the cultural historical development for the cultural historical development were analyzes of the tourism sector with the aim of favoring the economic development of the Pueblovejense sector by improving the quality of life. With the respective research and the data obtained after the online survey on how much the population knows about the cultural historical legacy of the poet Aurora Estrada for the development of Cultural Tourism. Allowing to know the Strategies of Diffusion and promote tourism about different writers from the Puebloviejo canton.